Network-Based Approach to Identify the Antiproliferative Mechanisms of Bruceine D in Breast Cancer From the Cancer Genome Atlas - Tian, Saisai; Jing, Rui; Zhang, Weidong (Frontiers in Oncology, 2020)
Bruceine D (BD) is a natural compound extracted from a Chinese herb Brucea javanica that has been used for anti-inflammatory and anti-cancer treatment. However, little is reported about BD’s effects in breast cancer tumorigenesis. In this paper, we aimed to investigate the effect of BD in breast cancer and elucidate the potential mechanism of BD by integrated multiple databases. Our data suggested BD inhibited MCF-7 and MDA-MB-231 cells proliferation and promoted cells apoptosis. We integrated multiple bioinformatics analysis strategies to identify genes, hub modules and pathways associated with BD treatment. Three key pathways, including AMIT_SERUM_RESPONSE_40_MCF10A, BILD_HRAS_ONCOGENIC_SIGNATURE and NAGASHIMA_NRG1_SIGNALING_UP were identified to be associated with therapeutic effects of BD in breast cancer. Additionally, we validated the key genes by using quantitative real-time PCR and western blot. In conclusion, these findings revealed potential molecular mechanisms of BD to treat breast cancer by affecting AMIT_SERUM_RESPONSE_40_MCF10A, BILD_HRAS_ONCOGENIC_SIGNATURE and NAGASHIMA_NRG1_SIGNALING_UP pathways and regulating expression of ZFP36, EGR1 and FOS.